Analysis Of Loop Unevenness Terry Fabrics. - Abdulaziz Dolimov; Raximjon Karimov; Muxammadyusuf Solijonov. (Zien Journals, 2022)
In terry fabrics, there are cut or loop piles of different heights, which are located in a certain order. The first reason for the unevenness of the length of the pile in terms of height is the unevenness of the linear density of the yarns of the warp and the weft. Secondly, the tension of the yarns also causes uneven pile.
Keywords: Fabric; pile; warp; weaving